Research Map on Islamic Wealth Management Studies - Mimma Maripatul Uula; Abrista Devi (SMART Insight, 2021)
Wealth has an important role in human life. For this reason, the role of good asset management is indispensable. Good wealth management is highly recommended in Islam. The purpose of this research is to see the development of IWM research around the world which is published by journals with that theme. This study used a qualitative method with a blibliometric analysis approach. The data used consists of 90 Scopus indexed research publications, then processed and analyzed using the VosViewer application with the aim of knowing the research development blibliometric map Islamic Wealth Management in this world. The results of the research explain related authors, institutions, countries and related keywords Islamic Wealth Management. Furthermore, the results of the bibliometric analysis author mapping Judging from the density of clusters, it shows the most authors publish their work on the theme Islamic Wealth Management are Muhamad n.h.n; Bakar, a.a. Abdullah a; Mirakhor a; Hanifm; Dan Alam n. The most publications related to IWM are INCEIF, Malaysia; Kansas State University, United; and Universiti Utara Malaysia. And for the countries with the most publications are Malaysia, Indonesia and the United States. Then, bibliometric analysis keywords mapping, four clusters were obtained which later became the research path.